Avaliação Bacteriológica da Água do Mar e dos Mexilhões Perna perna (Linnaeus, 1758) cultivados na Ilha Guaíba, Baía de Sepetiba, RJ - Pereira, Milena Marcela Domingues (2008)
The intensive use of Ilha Guaíba’s surrounding water for aquaculture has increased the demand for monitoring analyses to indicate the bacteriological environmental quality. In a year-long study developed from April 2007 to March 2008, total and fecal coliform concentrations present in superficial waters used for shellfish farming were determined by the Most Probable Number (MPN) technique. As well as that the screening for the presence of Salmonella and Staphylococcus positive coagulase which was also carried out. Total coliform values ranged from <1,80 a 9,43 x 10 NMP.100mL-1 and thermotolerant ones varied from < 1,8 e 2,71 x 10 NMP.100mL-1. Neither Salmonella nor Staphylococcus positive coagulase from shellfish growing water samples was isolated. The environmental factors, as superficial water temperature and salinity, rainfall and sunlight levels, Secchi profundity, were also measured. Annual averages for these factors were 23,1°C, 35,2, 5,1mm, 22,91W/m2 and 2,4m, respectively. Results have indicated an excellent bacteriological quality, proving that Ilha Guaíba’s water is in accordance with the Brazilian standards for shellfish growing areas. The main abiotic factor correlated with water contamination is rainfall followed by salinity